A de novo mutation in PITX2 underlies a unique form of Axenfeld-Rieger syndrome with corneal neovascularization and extensive proliferative vitreoretinopathy. (3rd July 2020) - Kletke, Stephanie N.; Vincent, Ajoy; Maynes, Jason T.; Elbaz, Uri; Mireskandari, Kamiar; Lam, Wai-Ching; Ali, Asim
ABSTRACT: Background: Axenfeld-Rieger syndrome is characterized by a spectrum of anterior segment dysgenesis involving neural-crest-derived tissues, most commonly secondary to mutations in the transcription factor genes PITX2 and FOXC1 . Materials and Methods: Single retrospective case report. Results: A full-term infant presented at 5 weeks of age with bilateral Peters anomaly and Axenfeld-Rieger syndrome, with development of atypical features of progressive corneal neovascularization and proliferative vitreoretinopathy. Despite surgical interventions, the patient progressed to bilateral phthisis bulbi by 22 months of age. Genetic testing revealed a novel de novo p.Leu212Valfs*39 mutation in PITX2, leading to loss of a C-terminal OAR domain that functions in transcriptional regulation. Conclusions: It is important to consider mutations in PITX2 in atypical cases of anterior segment dysgenesis that also present with abnormalities in the angiogenesis of the anterior and posterior segments.